Wudhu According to the Qur’an Hadith and Its Therapic Implementation for Schizophrenia Patients at the Jalma Sehat Kudus Rehabilitation Center - Umma Farida; Chusnul Warda Rahmah (MAGHZA, 2022)
Wudhu is a purification activity that is often carried out by Muslims every day, especially every time they want to pray. The Qur'an and hadith emphasize this command to perform ablution. Muslims majority view ablution as only a ritual obligation without understanding the benefits of ablution and its effects on mental health. This article aims to describe the urgency and benefits according to the Qur'an and hadith. Also, to explain the application of wudhu therapy for schizophrenic patients at the Jalma Sehat Kudus Rehabilitation Center. Schizophrenia is a severe mental disorder that affects the thoughts, feelings, and behavior of individuals. Schizophrenia is part of a psychotic disorder characterized by a loss of understanding of reality and self-awareness. This study is based on qualitative research with data collection methods using documentation, interviews, and observation techniques. The collected data is then analyzed by the inductive method. The results showed that wudhu therapy at the Jalma Sehat Rehabilitation Center was beneficial in stimulating the brain from the flow of water that flows from each ablution wash. Patients feel relaxed mind, heart, and soul supported by spiritual and medical treatment.